2007
DOI: 10.1093/icesjms/fsm173
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal relationships between the copepod community and hydrographic conditions in the southern East China Sea

Abstract: Lan, Y-C., Lee, M-A., Chen, W-Y., Hsieh, F-J., Pan, J-Y., Liu, D-C., and Su, W-C. 2008. Seasonal relationships between the copepod community and hydrographic conditions in the southern East China Sea. – ICES Journal of Marine Science, 65: 462–468. We studied the relationship between seasonal variation of the copepod community and hydrographic conditions in the southern East China Sea (ECS). Hydrographic conditions in the southwestern ECS were influenced by the China Coastal Current (CCC) from late autumn to ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…That project is intended to establish a long‐term hydrographic and biological database that can be used to construct numerical models for fisheries forecasts in the waters around Taiwan. Three related papers using the TaiCOFI data have been published [one on fish larvae (Hsieh et al , 2007) and two on copepods (Lan et al , 2008 a , b )]. Hsieh et al (2007) found that food sources might be a key factor to determine the abundance and distribution of fish larvae in winter (February 2003) in the waters around Taiwan.…”
Section: Introductionmentioning
confidence: 99%
“…That project is intended to establish a long‐term hydrographic and biological database that can be used to construct numerical models for fisheries forecasts in the waters around Taiwan. Three related papers using the TaiCOFI data have been published [one on fish larvae (Hsieh et al , 2007) and two on copepods (Lan et al , 2008 a , b )]. Hsieh et al (2007) found that food sources might be a key factor to determine the abundance and distribution of fish larvae in winter (February 2003) in the waters around Taiwan.…”
Section: Introductionmentioning
confidence: 99%
“…C. sinicus is the main food source for several fishes, such as anchovy (Engraulis japonicus Temminck & Schlegel, 1846), sardines (Sardina pilchardus Walbaum, 1792), sand eel (Ammodytes personatus Girard, 1856), and mackerel (Scomberomorus niphonius Cuvier, 1832), that are important for the fishing industry (Zhu & Iverson, 1990;Uye et al, 1999;Islam & Tanaka, 2008). Recent studies report that C. sinicus is abundant in the waters off Taiwan during winter and early spring, because of the incursion of cold water masses from the Yellow Sea and the East China Sea during the northeast (NE) monsoon period (September to April) by the China Coastal Current (Lee & Chao, 2003;Liang et al, 2003;Liu et al, 2003;Tseng & Shen, 2003;Hwang & Wong, 2005;Hwang et al, 2006;Dur et al, 2007;Lan et al, 2008). Therefore, we, along with others, consider this species a biological indicator for the intrusion of cold water into the northern part of the South China Sea (Hwang & Wong, 2005;Hwang et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Extensive studies have investigated the spatiotemporal variation in the abundance or composition of larval fish (Okazaki and Nakata 2007;Hsieh et al 2011;Lefébure et al 2013), zooplankton (e.g., Liao et al 2006;Lan et al 2008;Tseng et al 2008), and phytoplankton (e.g., Gong et al 2006;Liu et al 2010;Gong et al 2011) in the ECS. Many of these previous studies used the abundance of neighboring trophic levels to explain the variation of the focal study group, but the multi-level trophic interactions and the factors regulating them remained to be investigated.…”
Section: Introductionmentioning
confidence: 99%